Porous geopolymers as dye adsorbents: Review and perspectives. (10th November 2022) - Tochetto, G.A.; Simão, L.; de Oliveira, D.; Hotza, D.; Immich, A.P.S.
Abstract: The treatment of wastewater containing dyes remains a challenge for industries, and dye removal can become more complex depending on the chemical structure of the molecule. Conventional treatments are ineffective; therefore, there has been increasing research on alternative methods such as adsorption. Geopolymers have been used as adsorbents, especially for dye adsorption. In this work, we provide a systematic review of the synthesis, characterization, and application of geopolymers in dye adsorption. First, we describe the sources of geopolymers, such as aluminosilicates of natural origin or residues, including the methods of preparation and pore formation. Then, we critically discuss the basic characteristics of a good adsorbent, e.g., pore microstructure, surface area, functional groups, and mineralogical composition. We then evaluate the application of these materials for adsorption of different classes of dyes, in terms of color removal and adsorptive capacity. Furthermore, we address the mechanisms involved in sorption and briefly review studies on desorption and regeneration. Finally, we consider gaps to be filled, challenges to be overcome, and perspectives in order to guide and direct the development of more competitive adsorbent geopolymers. Graphical abstract: Image 1 Highlights: A systematic and bibliometric review on geopolymers was carried out. The main properties and characteristics of adsorbents was critically reviewed. The application of geopolymers in the adsorption of dyes was fully evaluated. Some gaps and challenges were found, so future perspectives were deeply discussed.